Banking Spreads in Latin America - Gelos, R. (IMF Working Papers; Working Paper ;, 2006)
Intermediation spreads in Latin America are high by international standards. This paper examines the determinants of bank interest margins in that region using bank and country-level data from 85 countries, including 14 Latin American economies. The results suggest that Latin America has higher interest rates, less efficient banks, and larger reserve requirements than other regions and that these factors have a significant impact on spreads. However, Latin American countries do not differ markedly from their peers in other aspects that are found important in determining the cost of financial intermediation, such as inflation and bank profit taxation.